2016
DOI: 10.1093/humupd/dmw008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hysteroscopy in improving reproductive outcomes of infertile couples: a systematic review and meta-analysis

Abstract: Robust and high-quality RCTs are still needed before hysteroscopy can be regarded as a first-line procedure in all infertile women, especially during the basal clinical assessment of the couple, when assisted reproductive treatment is not indicated yet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 67 publications
1
66
0
5
Order By: Relevance
“…In recent years, many reports have discussed noninvasive techniques that enable the monitoring of embryos' development without moving them from incubators, using time-lapse imaging, to increase the precision and sensitivity of embryo selection [30][31][32]. Besides the above evaluation criteria, the role of the clinician performing the transfer and the patient's inherent condition (endometrial receptivity) are additional key elements in determining the success of implantation, and should not be ignored [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many reports have discussed noninvasive techniques that enable the monitoring of embryos' development without moving them from incubators, using time-lapse imaging, to increase the precision and sensitivity of embryo selection [30][31][32]. Besides the above evaluation criteria, the role of the clinician performing the transfer and the patient's inherent condition (endometrial receptivity) are additional key elements in determining the success of implantation, and should not be ignored [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, limited evidence supports this proposal. Recent meta-analyses [8788] concerning hysteroscopy or artificial endometrial injuries in ART have reported significant improvements in the clinical pregnancy rate. However, this possibility has yet to be supported by well-designed RCTs, so this proposal must remain hypothetical for the time being.…”
Section: Treatment Of Cementioning
confidence: 99%
“…Infertility affects ~15% of couples who wish to have children and half of these cases are associated with male‐related factors 1. Genetic causes of azoospermia include chromosomal abnormalities, Y chromosome microdeletions, and specific mutations or deletions of several Y chromosomal genes 2, 3.…”
Section: Introductionmentioning
confidence: 99%